2022
DOI: 10.1108/bfj-03-2021-0281
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition among women and adolescent girls: impact of urbanization in rural–urban interface of Bangalore

Abstract: PurposeIndia is facing a double burden of malnutrition, i.e. undernutrition and obesity. Women and adolescent health and nutrition are very relevant issues which have not received much attention it deserves in India, especially in the context of a girl child. Hence, the purpose of this study is to assess malnutrition among women and adolescent girls as well as the associated factors.Design/methodology/approachAn attempt was made to assess malnutrition among women and adolescent girls and associated factors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Twenty‐one studies explored differences between rural and urban areas and the majority of them (16 studies) (Bellundagi et al, 2022; Bhargava et al, 2016; Biswas et al, 2017; Chakraborty et al, 2018; Ganie et al, 2017; Goonapienuwala et al, 2022; Harding et al, 2019; Hombaiah et al, 2021; Islam et al, 2020; Khan et al, 2022; Khatri et al, 2021; Mohan et al, 2019; Pandurangi et al, 2022; Prasad et al, 2016; Yadav et al, 2018; Young et al, 2020) found a higher prevalence of overweight and/or obesity in urban areas. Differences in overweight/obesity prevalence for males and females were inconsistent across studies; however, a pooled analysis combining 2416 population‐based measurements found that BMI was higher among girls compared to boys in South Asia (NCD Risk Factor Collaboration (NCD‐RisC), 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐one studies explored differences between rural and urban areas and the majority of them (16 studies) (Bellundagi et al, 2022; Bhargava et al, 2016; Biswas et al, 2017; Chakraborty et al, 2018; Ganie et al, 2017; Goonapienuwala et al, 2022; Harding et al, 2019; Hombaiah et al, 2021; Islam et al, 2020; Khan et al, 2022; Khatri et al, 2021; Mohan et al, 2019; Pandurangi et al, 2022; Prasad et al, 2016; Yadav et al, 2018; Young et al, 2020) found a higher prevalence of overweight and/or obesity in urban areas. Differences in overweight/obesity prevalence for males and females were inconsistent across studies; however, a pooled analysis combining 2416 population‐based measurements found that BMI was higher among girls compared to boys in South Asia (NCD Risk Factor Collaboration (NCD‐RisC), 2017).…”
Section: Resultsmentioning
confidence: 99%
“…No difference in underweight by gender was reported in one study (Verma et al, 2020 ). Underweight was reported as being greater among rural populations in three studies, reporting data from India, Pakistan and Bangladesh (Bellundagi et al, 2022 ; Khan et al, 2022 ; Wolf et al, 2020 ), compared to urban populations, while just one study, conducted in India (Tripathi & Chakravarti, 2022 ), reported a higher prevalence of underweight among urban, compared to rural populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is especially pronounced among the economically and socially disadvantaged and vulnerable sections (Bhattacharya et al ., 2019). Within these vulnerable sections, women are often identified and acknowledged as particularly affected (Bellundagi et al ., 2022). The pervasive gender-based discrimination in India, spanning from the ancient to the current times, results in numerous challenges for women, including in areas of education, occupation and nutrition (Choudhary and Singh, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The pervasive gender-based discrimination in India, spanning from the ancient to the current times, results in numerous challenges for women, including in areas of education, occupation and nutrition (Choudhary and Singh, 2018). Also, research on the interlinkages between child outcomes and parental characteristics indicates that children's outcomes, especially in education and health, heavily rely on their mother's educational and health status (Bellundagi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%